Perancangan Sistem Hibrid Berbasis Panel Surya dan LPG Sebagai Energi Alternatif Terbarukan - Pratama, Defrianto; Hadiningrum, Kunlestiowati; Muldiani, Ratu Fenny (Fakultas Teknik, Universitas Brawijaya, 2025)
A Hybrid System Based on Solar Panels and LPG offers an alternative energy solution that combines renewable solar energy with LPG for improved efficiency and reliability. Solar panels capture sunlight and convert it into electricity, which can be used immediately or stored in batteries for later use, such as at night or during cloudy weather. Solar energy is eco-friendly, renewable, and widely available. However, when solar energy is insufficient, LPG is used as a backup fuel for a generator to ensure continuous power supply. Although not renewable, LPG is cleaner than other fossil fuels like coal or oil. The hybrid system's advantage lies in its efficiency, as solar panels reduce LPG consumption, while LPG ensures uninterrupted power. This combination makes the system more reliable by providing energy even when one source is unavailable. Despite the use of LPG, this system is more environmentally friendly than relying solely on fossil fuels, as it reduces the overall need for LPG. Keywords: Solar Cells, LPG, Hybrid